2013
DOI: 10.1200/jco.2012.48.5748
|View full text |Cite
|
Sign up to set email alerts
|

Expectations About the Effectiveness of Radiation Therapy Among Patients With Incurable Lung Cancer

Abstract: A B S T R A C T PurposeAlthough radiation therapy (RT) can palliate symptoms and may prolong life, it is not curative for patients with metastatic lung cancer. We investigated patient expectations about the goals of RT for incurable lung cancers. Patients and MethodsThe Cancer Care Outcomes Research and Surveillance Consortium enrolled a population-and health system-based cohort of patients diagnosed with lung cancer from 2003 to 2005. We identified patients with stage wet IIIB or IV lung cancer who received R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 29 publications
2
84
1
1
Order By: Relevance
“…However, clinicians should assess these patients comprehensively and thoroughly, and make individual decisions accordingly. A clear definition and communication to the patient of the goals of the treatment is mandatory, in order to avoid inaccurate beliefs about the effects of the treatment (22). Other factors associated with the treatment, including the toxic side-effects of the therapy, time for the patient to travel to the hospital, cost of the therapy and absence of family members to provide support for the patient, must also be considered (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, clinicians should assess these patients comprehensively and thoroughly, and make individual decisions accordingly. A clear definition and communication to the patient of the goals of the treatment is mandatory, in order to avoid inaccurate beliefs about the effects of the treatment (22). Other factors associated with the treatment, including the toxic side-effects of the therapy, time for the patient to travel to the hospital, cost of the therapy and absence of family members to provide support for the patient, must also be considered (23).…”
Section: Discussionmentioning
confidence: 99%
“…33 Unfortunately, many patients believe inaccurately that therapy will be curative. For example, Chen et al 34 reported that 64% of patients with incurable lung cancer believed that radiation therapy could be curative, and Weeks et al 35 reported that 69% of patients with stage IV lung cancer and 81% of patients with stage IV colorectal cancer did not understand that chemotherapy was not curative. Delaying or avoiding E thical conflicts are among the most challenging situations faced by patients with life-threatening conditions, their families, health care providers, and the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…The IOM emphasized that patients with advanced cancer must be provided with palliative care, psychosocial support, and timely referral to hospice care for end-of-life care. Prior studies show that patients often have inaccurate perceptions about prognosis, leading to receipt of burdensome treatments at the end of life, 10,11 that patients may alter end-of-life treatment requests when adequately informed, 12 and that outcomes may be improved when patients engage in palliative care. 13 General internists are well positioned to offer a clinical perspective on the overall health status of those with advanced cancer and to discuss end-of-life care.…”
Section: Recommendations 1 and 2: Engaged Patientsmentioning
confidence: 99%